Monitoring neuromuscular function in sprinters using the countermovement jump: a longitudinal case study - Hasegawa, T.; Muratomi, K.; Furuhashi, Y.; Mizushima, J.; Maemura, H. (International Journal of Strength and Conditioning, 2025)
The countermovement jump (CMJ) is a widely used test for monitoring neuromuscular (NM) function. However, its suitability for longitudinal NM function monitoring in sprinters remains uncertain. This study examines the relationship between quantified training load and sprinters` CMJ performance over a 10-week training block. Five high-level male university sprinters participated in this longitudinal study and underwent CMJ testing once a week. Their training load was quantified using the weekly training impulse (wTRIMP) calculated from training duration and session rate of perceived exertion (RPE). Subjective wellness ratings (Wellness) were assessed using a 7-point scale questionnaire based on the Hooper-Mackinnon Questionnaire. Average weekly Wellness and CMJ variables were used for further analysis, examining their relationship with wTRIMP. During the monitoring period, 80-85% of participants` wTRIMP was attributed to sprint training. Significant relationships were observed between wTRIMP and CMJ variables in four out of five participants (e.g. Sub A: Eccentric Impulse; r = -0.814, p = 0.014, Sub B: Concentric Impulse; r = -0.775, p = 0.041, Sub C: Jump height; r = -0.704, p = 0.034, Concentric mean power; r = -0.825, p = 0.006, Sub E: Jump height; r = -0.723, p = 0.028, Concentric Impulse; r = -0.737, p = 0.024), with force-time related variables being more sensitive to wTRIMP than jump height. Additionally, a significant relationship between Wellness and wTRIMP was observed for only one sprinter (Sub A: Wellness; r = -0.620, p = 0.056), while no significant relationship was found for the remaining four sprinters. In conclusion, our results demonstrated that the CMJ is suitable for longitudinal NM function monitoring of sprinters.